Pantograph slide plate and preparation method thereof, and electrified transportation vehicle
By using graphite, electrolytic copper powder, resin binder and copper fiber materials, combined with pretreatment, hot press forming and calcining processes, pantograph skateboards with high strength and excellent wear resistance are prepared, which solves the problems of easy wear, easy breakage and large resistivity of existing skateboards, and extends their service life.
Patent Information
- Application Number
- CN202211546446.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-12-02
AI Technical Summary
Existing train pantograph skateboards are prone to electrical ablation and mechanical wear in harsh environments, resulting in a short service life and need to be replaced frequently.
Graphite, electrolytic copper powder, resin binder and copper fiber are used as the main materials to prepare pantograph skateboards through pretreatment, hot pressing and calcining processes to improve their strength, conductivity and wear resistance.
It significantly improves the strength and arc suppression performance of the pantograph skateboard, extends its service life, and reduces the replacement frequency.
Smart Images

Figure CN115971485B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials, and in particular relates to a pantograph slide plate and a preparation method thereof, and an electrified vehicle. Background Art
[0002] The electrification and high-speed development of railways are the overall development trends of the railway transportation industry, and the electrification of railway transportation is one of the important prerequisites for achieving the high-speed goal. During the operation of the train, the operating environment of the pantograph slide is relatively harsh. It is subjected to the physical and chemical effects of the natural environment for a long time. During the operation, various unexpected conditions such as electrical erosion and mechanical wear may occur with the contact wire due to various factors such as offline. The quality of the pantograph slide will directly affect its own replacement frequency and the service life of the contact wire. Therefore, more stringent requirements are put forward for the mechanical properties, electrical conductivity, wear resistance, etc. of the pantograph slide material.
[0003] In the prior art, the pantograph slide plate is generally made of copper alloy. When the electric locomotive is running at high speed, the pantograph slide plate obtains 100-1000A of current from the contact wire as the power supply of the locomotive in the sliding state, and friction loss is prone to occur in its working state. Since the pantograph slide plate works under relatively harsh conditions such as high speed, current carrying, high temperature, and low lubricity, the speed increase of high-speed electric trains will further shorten the service life of the pantograph slide plate, which will cause the pantograph slide plate to become the most frequently replaced component of the locomotive system.
[0004] With the development of polymer polymerization technology, more and more fields where metals are traditionally used are gradually being replaced by engineering plastics, especially in the field of friction-reducing and wear-resistant materials. Resin-type conductive composite materials are highly valued for their unique advantages such as high specific strength, strong designability, excellent friction-reducing and wear-resistant properties, good corrosion resistance, and convenience for large-area integral molding. Resin-type conductive composite materials have good controllability of structure and performance, and can adjust their electrical and mechanical properties within a large range. Summary of the invention
[0005] The invention provides a pantograph slide plate and a preparation method thereof, and an electrified vehicle using the pantograph slide plate, which are used to solve the problems of large adhesive wear, easy breakage under impact and high resistivity of the existing train pantograph slide plate.
[0006] The present invention provides a method for preparing a pantograph slide plate, the method comprising the following steps:
[0007] pre-treating the first material;
[0008] The pretreated first material is loaded into a mold at room temperature, a pressure of 150 MPa is applied to one side, and the mold is pressed at a temperature of 165±5° C. to obtain a second material;
[0009] The second material is isolated from air and slowly heated under medium protection, wherein the starting temperature of the slow heating is 130 degrees Celsius and the final temperature is 450-750 degrees Celsius;
[0010] The first material includes graphite, electrolytic copper powder, resin binder and copper fiber.
[0011] Preferably, the pre-processing of the first material comprises:
[0012] Degreasing, roughening and surface activation of graphite;
[0013] The treated graphite, electrolytic copper powder, resin binder and copper fiber are hot plate pressed at a temperature of 60±5°C, and then cooled and crushed.
[0014] Preferably, the treatment of the graphite further includes electrogalvanizing treatment or electrocopper plating treatment.
[0015] Preferably, the resin binder is a mixture of polybismaleimide resin and cashew nut shell oil-modified phenolic resin, cashew nut shell oil-modified phenolic resin, polyimide resin powder, and modified coal tar powder, and the mass fraction of the resin binder is 3%-13%.
[0016] Preferably, the mass fraction of the electrolytic copper powder is 63%-85%.
[0017] Preferably, the zinc content of the galvanized graphite is not more than 80%.
[0018] Preferably, the zinc content of the galvanized graphite is 46.71% or 78%.
[0019] Preferably, the electrolytic copper powder and the graphite are replaced by galvanized graphite.
[0020] The present invention also provides a pantograph slide plate, which is prepared by any of the above methods.
[0021] The present invention also provides an electrified vehicle using the pantograph slide plate.
[0022] The pantograph slide plate provided by the present invention has the advantages of high strength, strong designability, excellent friction reduction and wear resistance, good corrosion resistance and easy large-area integral molding. After being treated by a roasting process, the thermosetting resin therein undergoes a carbonization reaction to form hard resin carbon, which greatly improves the strength and arc suppression performance of the pantograph slide plate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0024] Figure 1 The data results of the wear rate test of each sample in Examples 1-4 of the present invention under the conditions of current flow and no current flow respectively;
[0025] Figure 2 The wear rate of each sample in Examples 5-9 of the present invention is tested under current and non-current conditions, and the obtained wear rate is a curve graph showing the change of the binder content;
[0026] Figure 3 is a graph showing the relationship between the galvanized graphite powder content and the wear rate of each sample in Examples 12-15 of the present invention;
[0027] Figure 4 is a graph showing the relationship between the final calcination temperature and the wear rate in Examples 16-19 of the present invention;
[0028] Figure 5 This is a SEM image of the damage morphology of the galvanized graphite-copper roasted type slide plate of Example 11 of the present invention;
[0029] Figure 6 This is an SEM image of the damage morphology of the ungalvanized graphite-copper roasted skateboard in Example 10 of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] A method for preparing a pantograph slide plate in the present invention comprises the following steps:
[0032] Step S1, pre-treating a first material, wherein the first material includes graphite, electrolytic copper powder, resin binder, and copper fiber.
[0033] The pretreatment of the graphite includes degreasing, roughening, and surfactant treatment, and the specific operations are as follows:
[0034] a. Oil removal: Heat 100g of graphite and 200ml of 10mol / L NaOH solution to a boil, and then keep warm for 20min. Then wash the graphite until it is neutral, filter it, and dry it for later use.
[0035] b. Roughening: Put the deoiled graphite into a beaker, add 200g of 98wt% concentrated sulfuric acid, heat to boil, and keep warm for 20min, then wash the graphite to neutrality for later use.
[0036] c. Surfactant treatment: Put the roughened graphite into a beaker, add 2g of sodium dodecylbenzene sulfonate to make a solution, soak for 30 minutes, wash until neutral, filter, and then dry at 120°C.
[0037] The treated graphite, electrolytic copper powder, resin binder and copper fiber are hot plate pressed at a temperature of 60±5°C, and then cooled and crushed.
[0038] Step S2, loading the pretreated first material into a mold at room temperature, applying a pressure of 150 MPa on one side, and pressing and molding at a temperature of 165±5° C. to obtain a second material;
[0039] Step S2 is a hot pressing step, in which the treated first material is loaded into a mold at room temperature, and the skateboard sample is pressed into shape by a single-side pressure method at a molding pressure of 150 MPa and a pressing temperature of 165±5°C.
[0040] To ensure that the gas generated during resin curing can be fully released and prevent defects, the mold is opened and deflated once every 10 seconds at the beginning of hot pressing, for a total of 3 times; in the subsequent pressure holding stage, the gas is deflated once every 3 minutes.
[0041] Step S3, isolating the second material from air and slowly heating it under medium protection, wherein the starting temperature of the slow heating is 130 degrees Celsius and the final temperature is 450-750 degrees Celsius;
[0042] Step S3 is a calcination step, in which the pressed skateboard sample is heated at a certain heating rate under air isolation and medium protection. To prevent the skateboard sample from cracking, the calcination temperature is slowly increased between 135 and 750°C.
[0043] The present invention provides a pantograph slide plate, which is prepared by the above method. The present invention provides the following examples to further illustrate the components, component contents and performance indicators of the pantograph slide plate used in the above method.
[0044] The pantograph slides prepared in Examples 1-4 all use 7% by mass of flake graphite, 5% of copper fiber, 81% of electrolytic copper powder, and 7% of resin material. The difference between Examples 1-4 is that different types of resin materials are used, including a mixture of PBMI (polybismaleimide resin) and YM resin (cashew nut shell oil modified phenolic resin), YM resin (cashew nut shell oil modified phenolic resin), high temperature P resin (polyimide resin powder, produced by Shanghai Resin Factory, model PC-8000), and MCTP powder (modified coal tar powder). The component contents of each embodiment are detailed in the table below:
[0045] Table 1 Formulation of Examples 1-4 of Pantograph Slide Plate Samples (mass %)
[0046]
[0047] The pantograph slide plate is prepared by the pantograph slide plate preparation method disclosed in the present invention, and the physical performance parameters such as volume density, room temperature resistivity, and Rockwell hardness thereof are tested and the results are as follows:
[0048] Table 2 Physical properties of different calcined skateboard samples
[0049]
[0050] At an ambient temperature of (25±2°C), air atmosphere, and a current density of 285A / cm 2 , sliding speed is 41.7m / s, wear time is 30min, loading load is 50N / cm 2 The current-carrying wear rate of Examples 1-4 was tested under the experimental conditions, and the results are shown in the attached Figure 1 As shown:
[0051] Under the same conditions, the current-carrying wear rates of different pantograph slides are greater than those of non-current-carrying slides. The current-carrying wear rates of the high-temperature P pantograph slide and the PBMI / YM pantograph slide are 9.75×10 -5 mm 3 / (N·m) and 6.51×10 -5 mm 3 / (N·m).
[0052] The current-carrying wear rate of the slide is closely related to its structural strength. When the high-temperature P resin is carbonized, volume shrinkage and obvious powdering occur, resulting in serious fragmentation of the continuous phase inside the slide matrix, loose structure, and non-denseness, with obvious delamination. However, the PBMI / YM pantograph slide has a high residual carbon rate after resin carbonization, and the formed resin carbon can be evenly dispersed in the copper matrix skeleton, so it is easier to produce chemical bonding at the interface, playing a role in hard carbon reinforcement.
[0053] Example 5-9: The content of the lubricating phase and the reinforcing phase is kept unchanged, and the content of the electrolytic copper powder in the components decreases with the increase of the binder content.
[0054] Table 3 Formulations of baked skateboards of different resin contents in Examples 5-9 (mass%)
[0055]
[0056] Note: The embodiment in which the PBMI / YM resin content is 7% is Example 1.
[0057] The pantograph slide plate is prepared by the pantograph slide plate preparation method disclosed in the present invention, and the physical performance parameters such as volume density, room temperature resistivity, and Rockwell hardness thereof are tested and the results are as follows:
[0058] Table 4 Physical properties of different calcined skateboards
[0059]
[0060] At an ambient temperature of (25±2°C), air atmosphere, and a current density of 285A / cm 2 , sliding speed is 41.7m / s, wear time is 30min, loading load is 50N / cm 2 Under the experimental conditions, the current-carrying wear rate comparison test of Examples 5-9 was carried out, and the results are as shown in the attached figure. Figure 2 Results for different fired skateboard specimens are shown.
[0061] The current-carrying wear rate of the slide plate shows a trend of decreasing first and then increasing with the increase of resin content. When the PBMI / YM resin content is 5 mass%, the current-carrying wear rate of the baked slide plate is the smallest. As the resin content increases, the content of fillers such as electrolytic copper powder decreases accordingly.
[0062] The volume density and hardness of the pantograph slide plate increase with the decrease of resin content, indicating that the densification degree and strength of the slide plate sample increase with the decrease of resin content. This can be considered to be due to the increase of metallurgical bonding strength between metal particles inside the slide plate caused by the replacement of the same volume fraction of resin by electrolytic copper powder.
[0063] Embodiment 10-12:
[0064] Furthermore, the formulations of experimental examples 10-12 of the pantograph slide plate samples in Table 5 were used, with PBMI / YM resin being used as a molding adhesive.
[0065] Table 5: Formulation of Examples 10-12 of Pantograph Slide Plate Samples (mass%)
[0066]
[0067]
[0068] The pantograph slide plate is prepared by the pantograph slide plate preparation method disclosed in the present invention. For Examples 11 and 12, the following operations are added in the pretreatment step:
[0069] d. Galvanizing: Add a certain amount of pretreated graphite powder to the solution after impurity removal and filtration, adjust the pH value of the solution, and then stir and ultrasonically oscillate for 60 minutes to evenly disperse the graphite for electroplating.
[0070] The results of testing the physical performance parameters of the pantograph slide plate prepared by the above method, such as volume density, resistivity, Rockwell hardness, and flexural strength, are as follows:
[0071] Table 6 Physical performance parameters of graphite-copper roasted skateboard
[0072]
[0073] It can be seen from Table 6 that the hardness and flexural strength of the galvanized graphite-copper roasted type skateboard are significantly better than those of the ungalvanized-copper roasted type skateboard, and the resistivity and flexural strength of the galvanized graphite-copper roasted type skateboard with high zinc content are better than those with low zinc content.
[0074] Embodiment 13-15:
[0075] Further, keeping the content of binder and reinforcing phase material unchanged, the content of electrolytic copper powder decreases with the increase of galvanized graphite content, and the formula (mass%) of Examples 13-15 of the pantograph slide plate sample in Table 7 is adopted. Among them, Example 15 is based on the preparation method used in Examples 11-12, and the galvanizing operation is changed to copper plating operation.
[0076] Table 7 Formulas of Examples 13-15 of Different Galvanized Graphite Powder Baking Type Skateboard Samples (mass%)
[0077]
[0078]
[0079] At an ambient temperature of (25±2°C), air atmosphere, and a current density of 285A / cm 2 , sliding speed is 41.7m / s, wear time is 30min, loading load is 50N / cm 2 Under the experimental conditions of the present invention, the current-carrying wear rate comparison test of Examples 12-15 was carried out, and the results are as shown in the attached figure. Figure 3 Results for different fired skateboard specimens are shown.
[0080] As the content of galvanized graphite powder increases, the current-carrying wear of the baked type slide plate first decreases and then increases. When the content of galvanized graphite powder is 30 mass%, the wear rate of the slide plate is the lowest. Under the condition of the same lubricating phase content, the current-carrying wear rate of the baked type slide plate made of galvanized graphite (Example 13) is significantly lower than the current-carrying wear rate of the baked type slide plate made of copper-plated graphite (Example 15).
[0081] Embodiment 16-19:
[0082] Furthermore, the formula of Example 13 was selected, and the final firing temperature was set at 470 degrees Celsius, 550 degrees Celsius, 630 degrees Celsius, and 710 degrees Celsius during firing to prepare pantograph slides.
[0083] Under the experimental conditions of ambient temperature (25±2°C), air atmosphere, current density of 285A / cm2, sliding speed of 41.7m / s, wear time of 30min, and load of 50N / cm2, the pantograph slide prepared by the methods of Examples 16-19 was subjected to a wear rate test experiment, and the results are shown in the attached figure. Figure 4 The results of slide plate samples with different final calcination temperatures are shown.
[0084] The wear rate of the pantograph slide plate shows a trend of first decreasing and then increasing with the increase of the final calcination temperature. With the increase of the final calcination temperature, the metallurgical bonding inside the slide plate becomes denser, and the wear resistance of the slide plate also increases accordingly. If the temperature is too low, an effective continuous phase cannot be formed; if the temperature is too high, the metal flow rate is accelerated, which causes uneven distribution of components inside the slide plate, and also forms micropores inside the slide plate, which hinder the free movement of electrons and split the network structure of metals such as copper, resulting in reduced wear resistance.
[0085] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structural transformation made by using the contents of the present invention and the drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention. The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structural transformation made by using the contents of the present invention and the drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
[0086] Matters not covered in the present invention are known technologies. The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention.
Claims
1. A method for preparing a pantograph slide plate, characterized in that: The method comprises the following steps: pre-treating the first material; The pretreated first material is loaded into a mold at room temperature, a pressure of 150 MPa is applied to one side, and the mold is pressed at a temperature of 165±5° C. to obtain a second material; The second material is isolated from air and slowly heated under medium protection, wherein the starting temperature of the slow heating is 130 degrees Celsius and the final temperature is 630 degrees Celsius; The first material includes graphite, 63% by mass of electrolytic copper powder, 5% by mass of a mixture of polybismaleimide resin and cashew nut shell oil-modified phenolic resin as a resin binder, and copper fiber; The pretreatment includes electrogalvanizing the graphite, and the first material after the pretreatment includes 30% by mass of galvanized graphite.
2. The preparation method according to claim 1, characterized in that: The pre-processing of the first material comprises: Degreasing, roughening and surface activation of graphite; The treated graphite, electrolytic copper powder, resin binder and copper fiber are hot plate pressed at a temperature of 60±5°C, and then cooled and crushed.
3. The preparation method according to claim 1, characterized in that: The zinc content of galvanized graphite is not more than 80%.
4. The preparation method according to claim 3, characterized in that: The zinc content of galvanized graphite is 46.71% or 78%.
5. A pantograph slide plate, prepared by any method of claims 1-4.
6. An electric vehicle using the pantograph slide plate as claimed in claim 5.
Citation Information
Patent Citations
Copper-coated short carbon fiber reinforced copper / graphite composite material and preparation method thereof
CN108930006A
Preparation method of roasting type composite pantograph slide plate
CN113997677A